ORGANIZATIONAL CULTURE, A PILLAR OF CORPORATE IDENTITY - Carmen RADU; Liviu RADU (Challenges of the Knowledge Society, 2025)
Organizational culture is an essential element in defining corporate identity, influencing a company's values, behaviors, and strategies. By analyzing cultural components and their impact on organizational performance, this study highlights how corporate identity is shaped by internal norms and practices. In a competitive environment, a strong culture can be a strategic advantage, strengthening employee cohesion and attracting partners and customers.